Heparanase is expressed in adult human osteoarthritic cartilage and drives catabolic responses in primary chondrocytes. Issue 8 (August 2018) - Gibor, G.; Ilan, N.; Journo, S.; Sharabi, A.; Dreyer, J.; Gertel, S.; Singh, P.; Menachem, A.; Snir, N.; Elkayam, O.; Vlodavsky, I.; Arad, U.
Summary: Objectives: The chondrocytes' pericellular matrix acts as a mechanosensor by sequestering growth factors that are bound to heparan sulfate (HS) proteoglycans. Heparanase is the sole mammalian enzyme with HS degrading endoglycosidase activity. Here, we aimed to ascertain whether heparanase plays a role in modulating the anabolic or catabolic responses of human articular chondrocytes. Methods: Primary chondrocytes were incubated with pro-heparanase and catabolic and anabolic gene expression was analyzed by quantitative polymerase chain reaction (PCR). MMP13 enzymatic activity in the culture medium was measured with a specific fluorescent assay. Extracellular regulated kinase (ERK) phosphorylation was evaluated by Western blot. Human osteoarthritis (OA) cartilage was assessed for heparanase expression by reverse-transcriptase PCR, by Western blot and by a heparanase enzymatic activity assay. Results: Cultured chondrocytes rapidly associated with and activated pro-heparanase. Heparanase induced the catabolic genes MMP13 and ADAMTS4 and the secretion of active MMP13, and down-regulated the anabolic genes ACAN and COL2A1 . PG545, a HS-mimetic, inhibited the effects of heparanase. Heparanase expression and enzymatic activity were demonstrated in adult human osteoarthritic cartilage. Heparanase induced ERK phosphorylation in cultured chondrocytes and this could be inhibited by PG545, by fibroblast growth factor 2 (FGF2) neutralizing antibodies and by a FGF-receptor inhibitor. Conclusions: Heparanase is active in osteoarthritic cartilage and induces catabolic responses in primary human chondrocytes. This response is due, at least in part, to the release of soluble growth factors such as FGF2.